Political influence on sportsmen's training system in olympic sports - T.K. Yessentayev (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to determine the place of Olympic sports in modern world; to analyze dynamic of its political, economic and social significance progress. Material: publications on the topic of this article were used as sources of information. Results: we characterized influence of Olympic sports on transformation of views and practical functioning in sphere of elite sportsmen's training. Main stages of modern Olympic sports' formation have been regarded. Strategy of elite sports' development in historical aspect has been presented. Changes in attitude of political leaders, state figures and general population to Olympic Games have been shown. Directions of development and perfection of elite sportsmen's training national systems have been outlined. Conclusions: recent years, potential of Olympic sports have being reflected in foreign and home policy of many countries. It resulted in drastic changes in spheres of organization, management, financing, material technical and personnel provisioning of sportsmen's training.